2011
DOI: 10.1007/s00109-011-0830-7
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia activates temporally coordinated transcriptional programs in visceral adipose tissue

Abstract: Obstructive sleep apnea (OSA) is a prevalent disorder characterized by intermittent hypoxia (IH) during sleep. OSA is strongly associated with obesity and dysregulation of metabolism-yet the molecular pathways linking the effects of IH on adipocyte biology remain unknown. We hypothesized that exposure to IH would activate distinct, time-dependent transcriptional programs in visceral adipose tissue of mice. We exposed 36 mice to IH or normoxia for up to 13 days. We transcriptionally profiled visceral fat tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 47 publications
(51 reference statements)
3
20
0
Order By: Relevance
“…This study confirms previous findings that chronic IH exposures imposed during the predominant sleep period in mice lead to the emergence of systemic insulin resistance and increased VWAT inflammation (11)(12)(13)(14)(15)(16)(17)(18). Furthermore, we now show that treatment with Resv improved the reduced food intake patterns and weight gain associated with IH-exposures and restored insulin responsiveness while normalizing the inflammatory processes within VWAT depots.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study confirms previous findings that chronic IH exposures imposed during the predominant sleep period in mice lead to the emergence of systemic insulin resistance and increased VWAT inflammation (11)(12)(13)(14)(15)(16)(17)(18). Furthermore, we now show that treatment with Resv improved the reduced food intake patterns and weight gain associated with IH-exposures and restored insulin responsiveness while normalizing the inflammatory processes within VWAT depots.…”
Section: Discussionsupporting
confidence: 91%
“…IH also imposes adverse metabolic consequences, such as hyperlipidemia and insulin resistance, even in lean mice, along with structural and cellular remodeling of adipose tissue (11)(12)(13)(14)(15)(16)(17)(18). The metabolic consequences of sleep apnea have been causally linked to increased prevalence and clinical deterioration of type 2 diabetes as well as with increased homeostatic model assessment of insulin resistance index (HOMA) in both children and adults (19 -24).…”
mentioning
confidence: 98%
“…Research on "-omics" (figure 1) continues, and may ultimately provide clinically useful biomarkers for adult [97] and paediatric [29,98,99] OSA. Examples are studies in adults and children with OSA using proteomics [29,100], studies on miRNA in patients with OSA and resistant hypertension [101], the application of system biology to genetic studies of OSA [102] and studies on visceral fat transcriptome to assess the molecular basis of the interaction between OSA and obesity [103,104]. A roadmap for a personalised approach to OSA has been proposed according to P4 medicine, ( personalisation, prediction, prevention and patient participation in healthcare) [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional profiling of visceral fat from mice exposed to IH revealed the differential expression of over 3000 genes, and gene-gene interaction network analyses showed that the most enriched pathways mapped to metabolic processes, mitochondrion and oxidative stress responses. Once again, the pathophysiological relevance was confirmed by demonstrating that these mice developed dyslipidaemia and underwent significant lipid and protein oxidation within their visceral adipose deposits 84. Exposure to IH will result in the mobilisation of very small embryonic-like pluripotent stem cells from the bone marrow to the peripheral blood 85.…”
Section: Genomic and Proteomic Approaches To Diagnosismentioning
confidence: 89%